2017
DOI: 10.1007/s00418-017-1581-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of markers for quiescent pancreatic stellate cells in the normal human pancreas

Abstract: Pancreatic stellate cells (PSCs) play a central role as source of fibrogenic cells in pancreatic cancer and chronic pancreatitis. In contrast to quiescent hepatic stellate cells (qHSCs), a specific marker for quiescent PSCs (qPSCs) that can be used in formalin-fixed and paraffin embedded (FFPE) normal human pancreatic tissue has not been identified. The aim of this study was to identify a marker enabling the identification of qPSCs in normal human FFPE pancreatic tissue. Immunohistochemical (IHC), double-IHC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 82 publications
3
29
0
Order By: Relevance
“…In contrast to quiescent hepatic stellate cells, immunohistochemical markers for quiescent pancreatic stellate cells in formaldehydefixed and paraffin-embedded human tissue are lacking. Using human tissue microarrays and an extensive panel of antibodies, Nielsen et al (2017) report now that cytoglobin and adipophilin are not only markers for quiescent hepatic but also for pancreatic stellate cells. Cytoglobin in human pancreas was expressed in two types of profibrogenic cells: quiescent stellate cells and resident interlobular fibroblasts.…”
Section: Immunohistochemical Markers For Quiescent Human Pancreatic Smentioning
confidence: 99%
“…In contrast to quiescent hepatic stellate cells, immunohistochemical markers for quiescent pancreatic stellate cells in formaldehydefixed and paraffin-embedded human tissue are lacking. Using human tissue microarrays and an extensive panel of antibodies, Nielsen et al (2017) report now that cytoglobin and adipophilin are not only markers for quiescent hepatic but also for pancreatic stellate cells. Cytoglobin in human pancreas was expressed in two types of profibrogenic cells: quiescent stellate cells and resident interlobular fibroblasts.…”
Section: Immunohistochemical Markers For Quiescent Human Pancreatic Smentioning
confidence: 99%
“…At present, there is no reliable marker to differentiate between quiescent stellate cells versus resident fibroblasts in the pancreas. 148 In this study, ultrastructurally, fibroblasts were identified in the control tissue, just few residing in inter-acinar spaces, containing no lipid droplets. Soon after insult, stellate cells were filled with RER and full and emptied lipid droplets but by day two of the experiments most of the stellate cells had no remaining lipid droplets.…”
Section: Fibrosismentioning
confidence: 58%
“…153 New special stains may aid in the identification of stellate cells in controls. 148 At the early stages of the experiments activating stellate cells were recognised by the presence of copious RER and lipid droplets in the cytoplasm and large regular shaped or elongated nuclei. The lipid droplets were seen up to three days in the CHB and duct ligation models, earlier in the caerulein model.…”
Section: Stellate Cells In Rat Modelsmentioning
confidence: 99%
See 2 more Smart Citations